Organizational compassion and employee adversarial growth under various job control - Nie, Ting; Zhao, Xinqiang; Zheng, Yanying (Frontiers in Psychology, 2023)
Introduction Adversity can bring stress and challenges to an individual's life, but many people who experience adversity also have positive changes. The formative mechanisms of individual adversarial growth have received widespread attention. Methods A two-wave survey of 421 Chinese employees who experienced adversity during the COVID-19 epidemic was used to examine the influence mechanism of organizational compassion on adversarial growth and the moderating effect of job control. Results Through correlation analysis, hierarchical regression, and bootstrap test on the cross-sectional data, the study has verified organizational compassion, work passion, self-worth, and adversarial growth form a chain mediating relation. Job control negatively moderates the indirect effect of organizational compassion on adversarial growth through work passion and self-worth, that is, the positive effect of organizational compassion on employee adversarial growth through work passion and self-worth is more pronounced under lower job control. Discussion Organizational compassion can increase employee adversarial growth by enhancing their work passion and self-worth. Organizations should also pay more attention to those employees with lower job control who are in adversity, they are more likely to benefit from the organization's care and compassion.